2019
DOI: 10.1021/acscatal.9b00790
|View full text |Cite
|
Sign up to set email alerts
|

Morphology Manipulation of Copper Nanocrystals and Product Selectivity in the Electrocatalytic Reduction of Carbon Dioxide

Abstract: We have revealed that cubelike and hexarhombic docadehedron-like Cu single crystals showed an enhancement of C2 products (ethylene and ethanol) while octahedron-like Cu nanoscale single crystals promoted C1 products of CO2 reduction. This product selectivity was revealed to be highly associated with the atomic arrangement on the surface. The remarkable high selectivity of ethanol (faraday efficiency of 25% with 14 mA/cm2, J ethanol ≈ 3.5 mA/cm2) for H–Cu was investigated and unraveled by using in situ X-ray ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
91
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 116 publications
(97 citation statements)
references
References 48 publications
6
91
0
Order By: Relevance
“…In contrast to the case of redox shuttle, the CO 2 reduction product through a conventional chronoamperometry (CA hereafter) at the same potential of −0.75 V was carbon monoxide ( Supplementary Fig. 5), which was characteristic of a copper-like behavior with the only product of CO from CO 2 RR at such potential 1,37 . The CuO x catalyst in present study gave a copper-like CO 2 RR performance once applying a higher cathodic potentials (higher than −0.95 V) where the dominant CO 2 RR product was CH 4 .…”
Section: And 2)mentioning
confidence: 95%
“…In contrast to the case of redox shuttle, the CO 2 reduction product through a conventional chronoamperometry (CA hereafter) at the same potential of −0.75 V was carbon monoxide ( Supplementary Fig. 5), which was characteristic of a copper-like behavior with the only product of CO from CO 2 RR at such potential 1,37 . The CuO x catalyst in present study gave a copper-like CO 2 RR performance once applying a higher cathodic potentials (higher than −0.95 V) where the dominant CO 2 RR product was CH 4 .…”
Section: And 2)mentioning
confidence: 95%
“…Compared to the C 1 products, only few kinds of catalysts have been reported to exhibit considerable selectivity to C 2 products, of which the copper‐based materials are the most attractive, especially for ethylene . Many pioneer researchers have studied the crystal structure effects of pristine copper towards CO 2 RR, where crystal planes, nanoparticle size and edge/corner morphologies are mostly discussed .…”
Section: Introductionmentioning
confidence: 99%
“…Many pioneer researchers have studied the crystal structure effects of pristine copper towards CO 2 RR, where crystal planes, nanoparticle size and edge/corner morphologies are mostly discussed . Chen et al . demonstrated that the atomic arrangements on Cu single crystal surfaces is crucial toward product selectivity of electrocatalytic CO 2 reduction.…”
Section: Introductionmentioning
confidence: 99%
“…A similar synthesis procedure was adopted by Suen et al to prepare their Cu nanocrystals with cubic, hexarhombic dodecahedron, and octahedron‐like morphologies. [ 56 ] The group modified the standard reflux setup by performing the reaction under N 2 gas at 230 °C (or 270 °C) for 3 h. Excess n‐hexane was used to wash the additives. HRTEM images of the above‐mentioned Cu nanostructures are shown in Figure a–d.…”
Section: Synthesis Of Cu‐based Catalystsmentioning
confidence: 99%
“…Reproduced with permission. [ 56 ] Copyright 2019, American Chemical Society. e) Various morphologies of Cu 2 O crystals.…”
Section: Synthesis Of Cu‐based Catalystsmentioning
confidence: 99%